A comparison of cardiopulmonary function, recovery quality, and total dosages required for induction and total intravenous anesthesia with propofol versus a propofol‐ketamine combination in healthy Beagle dogs. (21st July 2014) - Kennedy, Martin J; Smith, Lesley J
Abstract Objective To compare cardiopulmonary function, recovery quality, and total dosages required for induction and 60 minutes of total intravenous anesthesia (TIVA) with propofol (P) or a 1:1 mg mL−1 combination of propofol and ketamine (KP). Study design Randomized crossover study. Animals Ten female Beagles weighing 9.4 ± 1.8 kg. Methods Dogs were randomized for administration of P or KP in a 1:1 mg mL−1 ratio for induction and maintenance of TIVA. Baseline temperature, pulse, respiratory rate (fR), noninvasive mean blood pressure (MAP), and hemoglobin oxygen saturation (SpO2) were recorded. Dogs were intubated and spontaneously breathed room air. Heart rate (HR), fR, MAP, SpO2, end tidal carbon dioxide tension (Pe′CO2), temperature, and salivation score were recorded every 5 minutes. Arterial blood gas analysis was performed at 10, 30, and 60 minutes, and after recovery. At 60 minutes the infusion was discontinued and total drug administered, time to extubation, and recovery score were recorded. The other treatment was performed 1 week later. Results KP required significantly less propofol for induction (4.0 ± 1.0 mg kg−1 KP versus 5.3 ±1.1 mg kg−1 P, p = 0.0285) and maintenance (0.3 ± 0.1 mg kg−1 minute−1 KP versus 0.6 ±0.1 mg kg−1 minute−1 P, p = 0.0018). Significantly higher HR occurred with KP. Both P and KP caused significantly lower MAP compared to baseline. MAP was significantly higher with KP at several time points. P had minimal effects on respiratory variables, while KP resulted in significant respiratory depression. There were no significant differences in salivation scores, time to extubation, or recovery scores. Conclusions and clinical relevance Total intravenous anesthesia in healthy dogs with ketamine and propofol in a 1:1 mg mL−1 combination resulted in significant propofol dose reduction, higher HR, improved MAP, no difference in recovery quality, but more significant respiratory depression compared to propofol alone.